Akulturasi Budaya dalam Pernikahan Suku Karo dan Melayu - Aisyah, Nur; Harahap, Indra; Siregar, Husna Sari (ANWARUL, 2023)
This study examines cultural acculturation in Karo and Malay marriages. This research has several objectives for the researchers themselves and other students. The first to conduct this research is to find out about the process of acculturation between Karo and Malay ethnicities in Bela Rakyat Village, Kuala District, Langkat Regency, North Sumatra Province. The second objective is how the process of acculturation occurs in the culture of marriage that occurs between Karo and Malay ethnicities in Bela Rakyat Village, Kuala District, Langkat Regency, North Sumatra Province. Descriptive Qualitative research method. Qualitative Descriptive is an analysis that seeks to provide a detailed picture based on facts obtained from field facts and is also supported by primary and secondary data to support existing data. This qualitative research is presented in the form of a narrative and is assisted by the calculation of numbers, percentages, and entered in tables, then the data is entered in tables and the data will be analyzed descriptively so that in analyzing research problems it can be meaningful and can be explained and can answer what is be the problem. This research was conducted in Bela Rakyat Village. This field research showed that there were changes in social, cultural, and language forms. This is caused by several factors that influence the occurrence of cultural acculturation.